An Investigation into Tra Vinh University Second-Year English Majors’ Difficulties of Analyzing Shakespearean Plays in British Literature - Huynh Thi Diem Kieu (Trường Đại học Trà Vinh, 2018)
The main aim of this investigation is to find out some difficulties of English majors when learning British literature in general and in some Shakespearean plays in particular. Furthermore, the author bases on the elements as plot, character, setting, irony, subgenres, and themes in the drama analysis. For the reason why the author chose the topic for this thesis graduation, the author was strongly influenced by her academic background. Although English major students had the basic theory of drama analysis and gave the strategies from teachers, they also met a large number of problems in analyzing a play. Like the previous point, Vietnamese literature is not an easy subject for learners as well as British literature. Generally, the author was certain that it was necessary to investigate this field.